A REVIEW OF BURDEN OF CAREGIVERS OF PATIENTS WITH ALZHEIMER'S DISEASE - Ridzuan, Sayyidah Aqilah; Darussalam, Siti Eliza; Hisham, Nur Hazrina Mohamed; Namasivayam, Prashaantini; Nichole, Yam Min Yi; Zaid, Danial Syafiq Shahrir; Nor, Nurul Huda Mohd; Mohamed, Mohd Hazmi; Mooi, Ching Siew; Devaraj, Navin Kumar; Ismail, Iskasymar Bin Itam; Hashim, Hasnur Zaman; Mat, Liyana Najwa Inche; Kee, Hoo Fan; Basri, Hamidon; Sulaiman, Wan Aliaa Wan (Malang Neurology Journal, 2019)
Many are still unaware of the fact that Alzheimer’s disease (AD) also affects the caregivers quite significantly. Caregivers refer to people who are accountable of taking care of AD patients which provide helps with his or her daily living activities and may become a full-time commitment for the caregiver. This gives rise to a concept called caregiver burden. As these caregivers spend most of their time taking care of AD patients, most of them suffer psychologically as well as physically.Unfortunately, the risk of mental and physical impairment among the caregivers of Alzheimer’s patient may cause poor quality of life to both the patients and their caregivers. In addition, due to their role and responsibilities as a caretaker, they often do not have the opportunity to seek help and advices. This review article was conducted by sieving through numerous literature and studies regarding the challenges and how to help the burden of the caregivers of Alzheimer’s patients . This paper aims to give and overview, suggestions as well as to increase the awareness of the caregiver’s burden.